Autobiographical memory in the euthymic phase of recurrent depression. - Spinhoven, P; Bockting, C; Schene, A; Koeter, M; Wekking, E; Williams, J (2006)
The authors investigated autobiographical memory specificity in subjects who formerly had depression. In 122 euthymic patients with at least two previous major depressive episodes, memory specificity was significantly impaired compared to matched control participants but not related to residual symptoms and illness characteristics, was not differentially affected by cognitive therapy, and was also not predictive of relapse/recurrence during the 2-year follow-up. However, memory specificity was associated with age, education, and immediate and delayed memory recall. The results suggest that memory specificity may reflect a global cognitive impairment that remains in patients who (formerly) had depression but does not constitute a trait marker for vulnerability for relapse/recurrence.